Air pollution and myocardial infarction - Mehri F (Iran University of Medical Sciences, 1996)
Coronary artery disease is one of the main causes of mortality in most developed countries. There is also an increasing rate of mortality in developing countries where in addition to coronary artery disease, infection diseases still not have been controlled. Although, now a day coronary artery disease is responsible for half of deaths in developed countries, this regrettable event is increasing rapidly. It is predicted that by the year 2000 this disorder will spread dominantly in all developing countries and will cause many health problems. Although smoking is one of the main causes of stroke, coronary artery disease and other unfavorable effects on health, but recent studies show direct relationship between air pollution and prevalence of mortality due to coronary cardio pulmonary diseases. On the other hand, the principle which has been proved is that the negative effects of air pollution on heart and lung are more than other parts of human body.